Costos de producción de huevos: caso de estudio, granja avícola en el corregimiento Tablones – Palmira (2022)
The research presents a case study, where it aims to demonstrate how important it is for an entrepreneur to have an adequate production costing system, allowing dimensioning and knowing what to do to best maneuver any type of situation that can transcend the commercial.